ANALISIS LAPORAN KEUANGAN PT KERETA API INDONESIA (PERSERO) PERIODE 2020–2021 UNTUK MENGUKUR KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS - Maura Azhari, Dhea; Samri Juliati Nasution, Yenny (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
Analysis is used to assess the company's financial performance using its financial reports from different reporting periods. The general public, investors, shareholders and management can all benefit from financial company reports while making decisions and growing their own assets. This study will use financial measures based on liquidity ratios which include current ratios, quick ratios, and cash ratios to show the financial performance of the company PT Kereta Api Indonesia (Persero). The company's financial statements, which include an income statement and balance sheet for 2020-2021, are the subject of research. In this research data analysis used descriptive analysis using financial ratio analysis. Liquidity ratio consisting of current ratio (Current Ratio), quick ratio (Quick Ratio), and cash ratio (Cash Ratio) which is the basis for the results of financial ratio analysis